Method for producing separation membrane, separation membrane produced by said method, and electrochemical device including said separation membrane
By combining contact-type and non-contact dispersion equipment, the problem of shrinking or melting of the lithium-ion secondary battery separation membrane at high temperature is solved, and the uniform dispersion of silicone particles in the coating is achieved, thereby improving the thermal stability and ventilation of the battery.
Patent Information
- Application Number
- JP2024547910
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-14
- Filing Date
- 2023-02-14
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2043-02-14
AI Technical Summary
The separation membrane of existing lithium-ion secondary batteries is easily reduced or melted at high temperatures, causing positive and negative electrodes to contact each other, increasing the risk of explosion and combustion. At the same time, during the manufacturing process, it is difficult to achieve uniform dispersion of silicone particles in the coating, affecting the aeration and electrical conductivity of the separation membrane.
Using a combination of contact type and non-contact dispersion equipment, the silica gel particles are dispersed through large-particle beads in the contact type disperser, and further homogenize and disperse through a high-pressure homogenizer to ensure the uniform distribution of the silica gel particles in the coating.
It effectively improves the thermal stability and ventilation of the separation membrane, reduces the risk of short-circuiting of the battery at high temperatures, and improves the overall performance of the battery.
Smart Images

Figure 2025508710000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a separator that can be used in electrochemical devices such as lithium secondary batteries, a method for producing the separator, and an electrochemical device including the separator.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0019173, filed on February 14, 2022, the entire contents of which are incorporated herein by reference in their entirety in the specification and drawings. [Background technology]
[0003] Recently, interest in energy storage technology has been increasing. The fields of application are expanding to include mobile phones, camcorders, and notebook computers, as well as the energy of electric vehicles, and efforts in the research and development of electrochemical devices are gradually becoming more concrete. In this regard, electrochemical devices are the field that has attracted the most attention, and among them, rechargeable secondary batteries and lithium secondary batteries with high energy density have attracted attention. In addition, in the development of such secondary batteries, ensuring safety is a focus of attention.
[0004] In lithium secondary batteries currently in production, a polymeric porous support using a polyolefin polymer resin as a separator substrate is used to prevent short-circuiting between the positive and negative electrodes. However, the polymeric porous support has a problem of low heat resistance, as it shrinks or melts at high temperatures. Therefore, when the battery becomes hot due to internal / external stimuli, the separator shrinks or melts, etc., and the positive and negative electrodes come into contact with each other, which increases the possibility of a short circuit, and this can lead to a sudden release of electrical energy, which can cause the battery to explode or catch fire.
[0005] Therefore, in order to solve these problems, a method of improving heat resistance by forming an inorganic composite porous layer in which inorganic particles and a binder polymer are mixed on at least one surface of a polymeric porous support is widely used.
[0006] In the process of producing a slurry for forming an inorganic composite porous layer, inorganic particles and binder particles aggregate to form composite particles. In addition, the inorganic particles in the slurry aggregate, resulting in problems such as a decrease in air permeability and an increase in resistance. In an attempt to solve this problem, a milling process is performed in the conventional process for producing a separation membrane, in which inorganic particles in a slurry for forming an inorganic composite porous layer are crushed, mixed, and dispersed. However, it is difficult to ensure the dispersibility of the inorganic particles in the conventional milling process. Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a method for producing a separation membrane that can uniformly disperse inorganic particles in a slurry that forms an inorganic composite porous layer.
[0008] Another object of the present invention is to provide a separator having excellent physical properties and an electrochemical device including the separator.
[0009] It will be readily apparent that other objects and advantages of the present invention can be realized by the means or methods recited in the claims and combinations thereof. [Means for solving the problem]
[0010] The present inventors have found that the above-mentioned problems can be solved by the following method for producing a separator, a separator produced by the method, and an electrochemical device including the separator.
[0011] The first embodiment is (S1) preparing a slurry containing inorganic particles, a binder polymer, and a solvent; (S2) Dispersing inorganic particles in the slurry, The dispersion is carried out using two types of dispersion devices, a contact type disperser and a non-contact type disperser. the contact type dispersing machine includes beads having an average particle size of 200 times or more the average particle size (D50) of the inorganic particles; (S3) applying the slurry to at least one surface of a polymeric porous support and drying the slurry.
[0012] The second embodiment is the same as the first embodiment, The present invention relates to a method for producing a separation membrane, in which the contact type disperser contains beads having an average particle size that is 2000 to 4000 times the average particle size (D50) of the inorganic particles.
[0013] The third embodiment is the first or second embodiment, The present invention relates to a method for producing a separation membrane, in which the dispersion is first carried out using a contact type disperser and then carried out using a non-contact type disperser.
[0014] The fourth embodiment is the third embodiment, The present invention relates to a method for producing a separation membrane, in which after dispersion is performed using the contact disperser, the ratio of inorganic particles having a particle size distribution (PSD) of 10 times or more the average particle size (D50) of the inorganic particles in the slurry is 5% or less.
[0015] The fifth embodiment is any one of the first to fourth embodiments, The present invention relates to a method for producing a separation membrane, in which the contact type dispersing machine is a bead mill, a ball mill, a spike mill, a basket mill, an attrition mill, or two or more of these dispersing methods are applied.
[0016] The sixth embodiment is any one of the first to fifth embodiments, The present invention relates to a method for producing a separation membrane, wherein the non-contact type dispersing machine is a high-pressure homogenizer.
[0017] The seventh embodiment is any one of the first to sixth embodiments, The present invention relates to a method for producing a separation membrane, wherein the dispersion using the non-contact type disperser is carried out under a pressure condition of 5 MPa to 200 MPa.
[0018] The eighth embodiment is any one of the first to seventh embodiments, The present invention relates to a method for producing a separation membrane, wherein the beads have an average particle size (D50) of 0.5 mm or more.
[0019] The ninth embodiment is any one of the first to eighth embodiments, The present invention relates to a method for producing a separation membrane, wherein the beads are zirconia beads, alumina beads, yttria-stabilized zirconia (YSZ) beads, titania beads, or two or more of these.
[0020] The tenth embodiment is any one of the first to ninth embodiments, The present invention relates to a method for producing a separation membrane, wherein the inorganic particles have an average particle size of 0.01 μm to 1.0 μm.
[0021] The eleventh embodiment relates to a separation membrane manufactured by the method according to any one of the first to tenth embodiments.
[0022] The twelfth embodiment relates to an electrochemical device including a positive electrode, a negative electrode, and the separator of the eleventh embodiment interposed between the positive electrode and the negative electrode.
[0023] The thirteenth embodiment is the twelfth embodiment, The present invention relates to an electrochemical device, wherein the electrochemical device is a lithium secondary battery. Effect of the Invention
[0024] According to an embodiment of the present invention, a contact type dispersion method and a non-contact type dispersion method are used to disperse inorganic particles in a slurry, thereby providing a method for manufacturing a separator having improved dispersibility of inorganic particles by suppressing generation of secondary particles, removing coarse inorganic particles, and dispersing fine inorganic particles.
[0025] In addition, according to an embodiment of the present invention, a separator having excellent physical properties with reduced surface protrusion defects in appearance, and an electrochemical device including the separator can be provided.
[0026] The drawings attached to this specification are intended to illustrate preferred embodiments of the present invention and serve to further understand the technical ideas of the present invention as well as the contents of the invention, and therefore the present invention should not be interpreted as being limited to only the matters described in the drawings. Meanwhile, the shape, size, scale, or ratio of elements in the drawings attached to this specification may be exaggerated in order to emphasize a clearer description. [Brief description of the drawings]
[0027] [Figure 1] 1 shows the results of measuring the particle size distribution of the slurry dispersed in Example 1. [Diagram 2] 1 shows the results of measuring the particle size distribution of the slurry dispersed in Comparative Example 1. [Diagram 3] 1 shows the results of observing protrusions of the separator prepared in Comparative Example 1 using an SEM. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0028] The present invention will be described in detail below. The terms and words used in the present specification and claims should not be interpreted as being limited to their ordinary and dictionary meanings, but should be interpreted as having meanings and concepts that correspond to the technical ideas of the present invention, based on the principle that the inventor himself can appropriately define the concepts of terms in order to best describe the invention.
[0029] Throughout this specification, when a part "comprises" another component, it means that the part may further include the other component, not excluding the other component, unless otherwise specified.
[0030] Throughout this specification, the phrase "A and / or B" means "A, B, or both."
[0031] The separation membrane is manufactured by applying a slurry for forming an inorganic composite void layer to a polymeric porous support and drying it to form an inorganic composite void layer. If the slurry particles in the slurry for forming the inorganic composite void layer are not uniformly dispersed, the inorganic particles in the inorganic composite void layer aggregate with each other, which causes problems such as an increase in the resistance of the separation membrane or a decrease in air permeability. In the past, in order to solve such problems, a milling process was performed as a contact dispersion method in the process of manufacturing the slurry for forming the inorganic composite void layer. However, even after the milling process, there is a problem that the dispersibility of the inorganic particles in the slurry for forming the inorganic composite void layer is reduced. In particular, when performing the milling process, it is necessary to adjust the average particle size of the beads in consideration of the particle size of the fine inorganic particles in order to realize a desired particle distribution and to facilitate process management.
[0032] Meanwhile, a non-contact dispersion method has not been used in the technical field of producing separation membranes. However, the present inventors have found that by utilizing the non-contact dispersion method in the production of separation membranes, it is possible to apply a strong shear force to the fluid phase and uniformly disperse inorganic particles in the slurry.
[0033] In particular, the inventors have discovered a method for producing a separation membrane that can uniformly disperse inorganic particles during production by appropriately utilizing a contact dispersion method and a non-contact dispersion method to suppress the generation of secondary particles, remove coarse inorganic particles, and disperse fine inorganic particles.
[0034] According to an embodiment of the present invention, a method for producing a separation membrane includes the steps of: (S1) preparing a slurry containing inorganic particles, a binder polymer, and a solvent; (S2) Dispersing inorganic particles in the slurry, The dispersion is carried out using two types of dispersion devices, a contact type disperser and a non-contact type disperser. the contact type dispersing machine includes beads having an average particle size of 200 times or more the average particle size (D50) of the inorganic particles; (S3) applying the slurry to at least one surface of a polymeric porous support and drying the slurry.
[0035] In step (S1), a slurry containing inorganic particles, a binder polymer, and a solvent is prepared.
[0036] In a specific embodiment of the present invention, the slurry may be such that the inorganic particles are dispersed in the solvent and the binder polymer is dissolved in the solvent.
[0037] In a specific embodiment of the present invention, the inorganic particles are not particularly limited as long as they are electrochemically stable. That is, the inorganic particles that can be used in the present invention are not particularly limited as long as they do not undergo oxidation and / or reduction reactions within the operating voltage range of the electrochemical device to which they are applied (for example, 0 to 5 V based on Li / Li + reference). In particular, when using inorganic particles with a high dielectric constant as the inorganic particles, it is possible to contribute to an increase in the dissociation degree of electrolyte salts, such as lithium salts, in the liquid electrolyte and improve the ionic conductivity of the electrolyte solution.
[0038] For the reasons described above, the inorganic particles can be inorganic particles with a dielectric constant of 5 or more, inorganic particles having lithium ion transfer ability, or a mixture thereof.
[0039] The inorganic particles with a dielectric constant of 5 or more are one or more selected from the group consisting of Al2O3, SiO2, ZrO2, AlO(OH), TiO2, BaTiO3, Pb(Zr x Ti 1-x )O3 (PZT, 0 < x < 1), Pb 1-x La x Zr 1-y Ti y O3 (PLZT, 0 < x < 1, 0 < y < 1), (1 - x)Pb(Mg 1 / 3 Nb 2 / 3 )O3 - xPbTiO3 (PMN - PT, 0 < x < 1), hafnia (HfO2), SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZO3, and SiC, or a mixture of two or more thereof.
[0040] The inorganic particles having the lithium ion conduction ability are lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y (PO4)3, 0 < x < 2, 0 < y < 3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y -based glass (0 < x < 4, 0 < y < 13), lithium lanthanum titanate (Li x La y TiO3, 0 < x < 2, 0 < y < 3), lithium germanium thiophosphate (Li x Ge y P z S w , 0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), lithium nitride (Li x N y , 0 < x < 4, 0 < y < 2), SiS2-based glass (Li x Si y S z , 0 < x < 3, 0 < y < 2, 0 < z < 4), and P2S5-based glass (Li x P y S z , 0 < x < 3, 0 < y < 3, 0 < z < 7) and may be one or a mixture of two or more selected from the group consisting of.
[0041] Also, the average particle size (D50) of the inorganic particles is not particularly limited, but for the formation of a coating layer having a uniform thickness and an appropriate porosity, those having an average particle size of 0.01 μm or more and 0.5 μm or more can be used, and those having an average particle size of 10 μm or less, 5 μm or less, or 1 μm or less can also be used. The numerical range of the average particle size can be any combination of the above upper and lower limits. In the present invention, the average particle size (D50) means the particle size at the 50% point of the cumulative particle number distribution according to the particle size.
[0042] In a specific embodiment of the present invention, the binder polymer may be a binder polymer that is commonly used in the art for forming an inorganic composite porous layer when manufacturing a separator. g ) may be used, which can improve the mechanical properties such as flexibility and elasticity of the inorganic composite porous layer that is finally formed. Such a binder polymer sufficiently plays the role of a binder that connects and stably fixes inorganic particles to each other, thereby contributing to preventing a decrease in the mechanical properties of the separation membrane in which the inorganic composite porous layer is introduced.
[0043] In addition, the binder polymer does not necessarily have to have ion-conducting ability, but when a polymer having ion-conducting ability is used, the performance of the electrochemical element can be further improved. Therefore, the binder polymer can be used with a dielectric constant as high as possible. Since the degree of dissociation of salt in an electrolyte actually depends on the dielectric constant of the electrolyte solvent, the higher the dielectric constant of the binder polymer, the more the degree of dissociation of salt in the electrolyte can be improved. The dielectric constant of such a binder polymer can be in the range of 1.0 to 100 (measurement frequency = 1 kHz), and can be particularly 10 or more.
[0044] In addition to the above-mentioned functions, the binder polymer may have a feature of exhibiting a high degree of swelling in the liquid electrolyte by gelling when immersed in the liquid electrolyte. Accordingly, the solubility index, i.e., Hildebrand solubility index, of the binder polymer is 15 to 45 MPa. 1 / 2 , 15~25MPa 1 / 2 , or 30 to 45 MPa 1 / 2 Therefore, a hydrophilic polymer having more polar groups can be used rather than a hydrophobic polymer such as polyolefins. 1 / 2 Less than or 45MPa 1 / 2 If the amount is excessive, it is difficult for the material to swell due to a typical liquid electrolyte for batteries.
[0045] Non-limiting examples of such binder polymers include polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polyethylhexyl acrylate, polybutyl acrylate, polyacrylonitrile, polyvinylpyrrolidone, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, and carboxymethyl cellulose, but are not limited thereto.
[0046] The weight ratio of the inorganic particles to the binder polymer is, for example, 50:50 to 99:1, specifically 70:30 to 95:5. When the content ratio of the inorganic particles to the binder polymer satisfies the above range, the problem of a decrease in pore size and porosity of the inorganic composite porous layer formed due to an increase in the binder polymer content can be prevented, and the problem of a decrease in peel resistance of the inorganic composite porous layer formed due to an increase in the binder polymer content can be resolved.
[0047] In the method for manufacturing a separator according to an embodiment of the present invention, the inorganic composite porous layer may further include other additives, such as a dispersant, in addition to the inorganic particles and binder polymer described above.
[0048] In a specific embodiment of the present invention, the solvent is a liquid capable of dissolving the binder polymer, and is not particularly limited as long as it is a liquid commonly used in the art.
[0049] Non-limiting examples of the solvent include acetone, tetrahydrofuran, methylene chloride, chloroform, trimethyl phosphate, triethyl phosphate, methyl ethyl ketone (MEK), toluene, hexane, cyclohexane, dimethylformamide (DMF), dimethylacetamide (DMAc), N-methyl-2-pyrrolidone (NMP), or a mixture of two or more of these, and preferably acetone. Non-limiting examples of the solvent include water, methanol, ethanol, ethylene glycol, diethylene glycol, glycerol, which are aqueous solvents, or a mixture of two or more of these.
[0050] Next, in step (S2), two types of dispersing devices, a contact type disperser and a non-contact type disperser, are used together to disperse the inorganic particles in the slurry. In the present invention, the inorganic particles can be uniformly dispersed in the slurry by appropriately utilizing the contact type disperser and the non-contact type disperser.
[0051] In a specific embodiment of the present invention, the inorganic particles in the slurry can be dispersed by first dispersing them with a contact disperser and then dispersing them with a non-contact homogenizer. After removing the coarse inorganic particles with the contact disperser, the non-contact homogenizer can achieve a more uniform particle size, and sufficient shear force can be applied to the inorganic particles in the non-contact homogenizer, making it easier to disperse the fine inorganic particles.
[0052] After dispersion using the contact type disperser, the particle size distribution (PSD) of the inorganic particles in the slurry may show that the ratio of inorganic particles having a particle size 10 times or more the average particle size (D50) of the inorganic particles in the average particle size distribution may be 5% or less.
[0053] The contact type disperser is a device that can pulverize and disperse inorganic particles by physical impact between the beads and the inorganic particles inside a device that contains a slurry containing inorganic particles and beads. For example, the contact type disperser may be a bead mill, a ball mill, a spike mill, a basket mill, an attrition mill, or a dispersing method that applies two or more of these.
[0054] For example, the contact type disperser may be a bead mill disperser that applies a bead mill dispersion method. The bead mill disperser may be a device that can disperse inorganic particles while pulverizing them using a bead mill method. The type of the bead mill disperser is not particularly limited as long as it is one that is commonly used in the art.
[0055] Meanwhile, the contact type disperser of the present invention includes beads having an average particle size of 200 times or more the average particle size (D50) of the inorganic particles. Specifically, the average particle size of the beads may be 200 to 4000 times, or 2000 to 4000 times, the average particle size of the inorganic particles. In addition, the average particle size of the beads may be 200 times or more the average particle size of the inorganic particles, and may be 0.5 mm or more, specifically 0.5 mm or more and 1.5 mm or less. By including beads that satisfy the above-mentioned predetermined average particle size range in the bead mill disperser, a desired particle distribution can be realized, and sufficient impact force can be applied to the inorganic particles, so that the generation of secondary particles can be suppressed. In addition, the dispersed inorganic particles and the beads can be easily separated. In particular, when beads smaller than the proposed average particle size are used, process control is difficult, and there is a risk of problems occurring in the quality of the separation membrane due to the generation of secondary particles that are not completely crushed due to insufficient impact force.
[0056] The type of the beads is not particularly limited, but is preferably one that can improve the dispersibility of inorganic particles by colliding with the inorganic particles in the slurry. For example, the beads may be zirconia beads, alumina beads, yttria-stabilized zirconia (YSZ) beads, titania beads, or two or more of these.
[0057] In the present invention, the non-contact type dispersing machine may be a high-pressure homogenizer.
[0058] The high-pressure homogenizer is a device that homogenizes a material by applying high pressure to a fine flow path and applying a strong shear force to the material passing through the flow path. By homogenizing the slurry using a high-pressure homogenizer, inorganic particles in the slurry can be uniformly dispersed. This has an advantage over the contact type dispersion method using beads in that it can disperse fine particles that are difficult to apply physical impact due to the size of the beads used in the contact type dispersion machine.
[0059] Dispersion by the high-pressure homogenizer can be performed by applying a high pressure of 5 MPa or more, or a high pressure in the range of 5 MPa to 200 MPa, more preferably a high pressure in the range of 10 MPa to 50 MPa to the fluid. By performing dispersion under such conditions, a sufficient dispersion force capable of dispersing the secondary particles can be imparted, and at the same time, the durability of the device can be ensured.
[0060] Then, in step (S3), the slurry is applied to at least one surface of a polymeric porous support and dried.
[0061] The method of coating the inorganic composite porous layer-forming composition on the polymeric porous support is not particularly limited, but it is preferable to use a slot coating or dip coating method. Slot coating is a method in which the composition supplied through a slot die is applied to the entire surface of the substrate, and the thickness of the coating layer can be adjusted depending on the flow rate supplied by a metering pump. Dip coating is a method in which the substrate is immersed in a tank filled with the composition to coat it, and the thickness of the coating layer can be adjusted depending on the concentration of the composition and the speed at which the substrate is pulled up from the composition tank. After immersion, the substrate may be post-weighed using a Mayer bar or the like to more accurately control the coating thickness.
[0062] The polymeric porous support coated with the composition for forming an inorganic composite porous layer is dried using a dryer such as an oven to form an inorganic composite porous layer formed on at least one surface of the polymeric porous support.
[0063] In the inorganic composite porous layer, inorganic particles are packed together and in contact with each other, and are bound to each other by the binder polymer, forming interstitial volumes between the inorganic particles, which become empty spaces to form pores.
[0064] That is, the binder polymer adheres the inorganic particles so that they are kept bound together, for example, the binder polymer connects and fixes the inorganic particles together. Also, the pores of the inorganic composite porous layer are pores formed when the interstitial volumes between the inorganic particles become vacant spaces, and these may be spaces limited by inorganic particles that are substantially in contact with each other in a packed structure of inorganic particles (closed packed or densely packed).
[0065] In the electrode assembly according to the present invention, the polymeric porous support may be specifically a porous polymeric film substrate or a porous polymeric nonwoven fabric substrate.
[0066] The porous polymer film substrate may be a porous polymer film made of polyolefin such as polyethylene or polypropylene, and such a polyolefin porous polymer film substrate exhibits a shutdown function at a temperature of, for example, 80°C to 130°C.
[0067] In this case, the polyolefin porous polymer film may be formed from a polyolefin polymer such as polyethylene (high density polyethylene, linear low density polyethylene, low density polyethylene, ultra-high molecular weight polyethylene), polypropylene, polybutylene, polypentene, or a mixture of two or more of these polymers.
[0068] In addition, the porous polymer film substrate may be manufactured by forming various polymers such as polyester, in addition to polyolefin, into a film shape. In addition, the porous polymer film substrate may be formed in a structure in which two or more film layers are laminated, and each film layer may be formed from the above-mentioned polymers such as polyolefin and polyester alone or a mixture of two or more of them.
[0069] In addition, the porous polymer film substrate and the porous nonwoven fabric substrate may be formed from a polymer such as polyethylene terephthalate, polybutylene terephthalate, polyester, polyacetal, polyamide, polycarbonate, polyimide, polyether ether ketone, polyether sulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthalate, etc., either alone or in combination, in addition to the above-mentioned polyolefin-based polymers.
[0070] The thickness of the polymeric porous support is not particularly limited, but is preferably 1 μm to 100 μm, more preferably 5 μm to 50 μm. The pore size and porosity of the polymeric porous support are also not particularly limited, but are preferably 0.01 μm to 50 μm and 10% to 95%, respectively.
[0071] A separator according to another embodiment of the present invention is a separator manufactured by the manufacturing method according to an embodiment of the present invention. The separator manufactured by the above-mentioned manufacturing method exhibits low resistance and prevents internal short circuits caused by undispersed coarse particles because the inorganic particles in the inorganic composite porous layer do not aggregate and the pore distribution formed by the interstitial volume between the inorganic particles is uniform.
[0072] According to another embodiment of the present invention, there is provided an electrochemical device including a positive electrode, a negative electrode, and a separator interposed between the positive electrode and the negative electrode, the separator being manufactured by the above-described method for manufacturing a separator.
[0073] Such electrochemical devices include all devices that perform electrochemical reactions, and specifically include all types of primary batteries, secondary batteries, fuel cells, solar cells, and capacitors such as supercapacitor devices, etc. In particular, among the secondary batteries, lithium secondary batteries including lithium metal secondary batteries, lithium ion secondary batteries, lithium polymer secondary batteries, and lithium ion polymer secondary batteries are preferred.
[0074] The positive and negative electrodes to be used with the separator of the present invention are not particularly limited, and may be prepared by a conventional method known in the art in the form of an electrode active material bound to an electrode current collector. Non-limiting examples of the positive electrode active material among the electrode active materials include conventional positive electrode active materials used in the positive electrode of conventional electrochemical devices, and in particular, lithium manganese oxide, lithium cobalt oxide, lithium nickel oxide, lithium iron oxide, or a lithium composite oxide made by combining these materials. Non-limiting examples of the negative electrode active material include conventional negative electrode active materials used in the negative electrode of conventional electrochemical devices, and in particular, lithium metal or lithium alloys, carbon, petroleum coke, activated carbon, graphite, or other carbons, and other lithium adsorbents, and the like are preferred. Non-limiting examples of the positive electrode current collector include foils made of aluminum, nickel, or a combination thereof, and non-limiting examples of the negative electrode current collector include foils made of copper, gold, nickel, or a copper alloy, or a combination thereof.
[0075] The electrolyte used in the electrochemical element of the present invention is A + B - A salt having the structure: + Li + , Na + , K+ or a combination thereof, - PF6 - , BF4 - , Cl - , Br - , I - , ClO4 - , AsF6 - , CH3CO2 - , CF3SO3 - , N(CF3SO2)2 - , C(CF2SO2)3 - or a combination thereof, dissolved or dissociated in an organic solvent such as, but not limited to, propylene carbonate (PC), ethylene carbonate (EC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), dimethyl sulfoxide, acetonitrile, dimethoxyethane, diethoxyethane, tetrahydrofuran, N-methyl-2-pyrrolidone (NMP), ethyl methyl carbonate (EMC), gamma butyrolactone (γ-butyrolactone), or a mixture thereof.
[0076] The electrolyte may be injected at an appropriate stage in the battery manufacturing process depending on the manufacturing process and desired properties of the final product, i.e., before battery assembly or at the final stage of battery assembly.
[0077] The present invention will be described in detail below with reference to specific examples. However, the examples according to the present invention can be modified into many other forms, and the scope of the present invention should not be construed as being limited to the following examples. The examples of the present invention are provided to more completely explain the present invention to those skilled in the art.
[0078] [Example] The separation membranes of the respective Examples and Comparative Examples were produced by the following method.
[0079] <Example 1> 1) At room temperature, Al2O3 inorganic particles (Daehan Ceramics, ALK-N1, average particle size 280 nm), polyvinylidene fluoride (PVDF) binder polymer, and cyanoethyl pullulan were added to acetone and stirred to prepare a slurry. The inorganic particles:PVDF:cyanoethyl pullulan:acetone content was 23:6:1:70 by weight.
[0080] 2) The slurry was charged into a bead mill disperser, which was equipped with zirconia beads having an average particle size of 0.6 mm, and dispersed at 50° C. for 3 hours.
[0081] After dispersion was performed using a bead mill disperser, dispersion was further performed using a high-pressure homogenizer under a pressure condition of 20 MPa.
[0082] 3) The dispersed slurry was applied to one side of a polyethylene porous film SW811G (Senior Corporation, thickness 11 μm, porosity 48%) and then dried to prepare a separator.
[0083] <Example 2> A separation membrane was produced in the same manner as in Example 1, except that zirconia beads having an average particle size of 1.0 mm were used in the bead mill disperser.
[0084] <Comparative Example 1> A separation membrane was produced in the same manner as in Example 1, except that zirconia beads having an average particle size of 0.8 mm were used in the bead mill disperser and the high-pressure homogenizer was not used.
[0085] <Comparative Example 2> A separation membrane was produced in the same manner as in Example 1, except that zirconia beads having an average particle size of 0.1 mm were used in the bead mill disperser.
[0086] <Comparative Example 3> Except for using only the high-pressure homogenizer, the slurry was produced in the same manner as in Example 1. The flow path of the high-pressure homogenizer was clogged by inorganic particles that could not be dispersed during the production process, making continuous production impossible.
[0087] <Experimental Results>
[0088] [Table 1]
[0089] (1) Slurry particle size and particle size standard excess rate (%) The particle size distribution of the dispersed slurry was measured, and D50 and D90 were calculated from a particle size distribution graph versus volume. Figures 1 and 2 show particle size distribution graphs of the slurries dispersed in Example 1 and Comparative Example 1.
[0090] D50 indicates the particle size at 50% of the maximum particle size based on the total volume of the graph, and D90 indicates the particle size at 90% of the maximum particle size based on the total volume of the graph. In other words, when the graph is divided into 10 equal parts based on the cumulative particle size distribution chart, it indicates the particle size at 5 / 10 and 9 / 10.
[0091] - The particle size exceedance ratio in Table 1 indicates the ratio of inorganic particles having a particle size 10 times or more the average particle size (D50) of inorganic particles in the particle size distribution (PSD) of inorganic particles in the slurry.
[0092] (2) Appearance (surface protrusions) evaluation method A 1m x 1m separation membrane was sampled, and the corresponding area was visually inspected for protrusions to determine whether it was a good product or not. (Judgment criteria: OK: no protrusions, NG: protrusions observed visually)
Claims
1. (S1) preparing a slurry containing inorganic particles, a binder polymer, and a solvent; (S2) Dispersing inorganic particles in the slurry, The dispersion is carried out using two types of dispersion devices, a contact type disperser and a non-contact type disperser. the contact type dispersing machine includes beads having an average particle size of 200 times or more the average particle size (D50) of the inorganic particles; (S3) applying the slurry to at least one surface of a polymeric porous support and drying the slurry.
2. The method for producing a separation membrane according to claim 1, wherein the contact type disperser contains beads having an average particle size 2000 to 4000 times the average particle size (D50) of the inorganic particles.
3. The method for producing a separation membrane according to claim 1 , wherein the dispersion is carried out by first using a contact type disperser and then using a non-contact type disperser.
4. 4. The method for producing a separation membrane according to claim 3, wherein after dispersion is performed using the contact disperser, in a particle size distribution (PSD) of inorganic particles in the slurry, a ratio of inorganic particles having a particle size 10 times or more the average particle size (D50) of the inorganic particles is 5% or less.
5. The method for producing a separation membrane according to claim 1 , wherein the contact type disperser is a bead mill, a ball mill, a spike mill, a basket mill, an attrition mill, or two or more of these dispersing methods are applied.
6. The method for producing a separation membrane according to claim 1 , wherein the non-contact type dispersing machine is a high-pressure homogenizer.
7. The method for producing a separation membrane according to claim 1, wherein the dispersion using the non-contact type disperser is carried out under a pressure condition of 5 MPa to 200 MPa.
8. The method for producing a separation membrane according to claim 1, wherein the beads have an average particle size (D50) of 0.5 mm or more.
9. 2. The method for producing a separation membrane according to claim 1, wherein the beads are zirconia beads, alumina beads, yttria-stabilized zirconia (YSZ) beads, titania beads, or two or more of these.
10. The method for producing a separation membrane according to claim 1, wherein the inorganic particles have an average particle size of 0.01 μm to 1.0 μm.
11. A separation membrane produced by the method according to any one of claims 1 to 10.
12. An electrochemical device comprising a positive electrode, a negative electrode, and the separator according to claim 11 interposed between the positive electrode and the negative electrode.
13. The electrochemical device according to claim 12, wherein the electrochemical device is a lithium secondary battery.
Citation Information
Patent Citations
Lithium ion battery ceramic separation membrane slurry and preparation method thereof
CN108417758A
Lithium battery diaphragm with high temperature resistance and high electrolyte wettability and preparation method thereof
CN111816825A
Slurry and method of manufacturing separator for nonaqueous electrolyte secondary battery using that slurry
JP2012094493A
Production method of laminate porous film
JP2014040580A
Method for manufacturing slurry for porous film, and slurry for porous film
JP2015065097A